G276T polymorphism in the ADIPOQ gene is associated with a reduced risk of polycystic ovarian syndrome: A meta-analysis of Asian population - Raphael Enrique Tiongco; Franzielle Jowe Cabrera; Benjie Clemente; Chastene Christopher Flake; Micah Angela Salunga; Maria Ruth Pineda-Cortel (Elsevier, 2019)
Objective: The etiology of polycystic ovarian syndrome (PCOS) has not yet been fully explained. Several studies suggested an association between two single nucleotide polymorphisms (T45G and G276T) of the ADIPOQ gene that encodes for the hormone adiponectin and PCOS susceptibility. Hence, we performed a meta-analysis to investigate the relationship of the two further. Materials and methods: Literature search was conducted in PubMed up to June 22, 2018, for related publications written in English. Selected data were extracted from the included studies and was subjected to analysis using Review Manager 5.3. Odds ratios (ORs) and 95% confidence intervals (CIs) were computed and pooled from the resulting studies. Subgroup analysis by ethnicity was also performed. Results: Overall analysis showed that women with the G276T polymorphism have reduced susceptibility to PCOS (OR: 0.68; 95% CI: 0.60-0.78; PA < 0.001). While no significant association was observed for the T45G polymorphism (OR: 1.07; 95% CI: 0.93-1.24; PA = 0.34). Subgroup analysis, on the other hand, showed significant associations among East Asians (OR: 0.69; 95% CI: 0.57-0.82; PA < 0.001) for the G276T association. Conclusion: Results of this meta-analysis suggests that women with the G276T polymorphism are less likely to develop PCOS. However, more studies are needed to confirm the claims of this meta-analysis. Keywords: G276T, T45G, Polycystic ovarian syndrome, Adiponectin gene, Meta-analysis